Implementation of Information Technology in Increasing the Efficiency and Effectiveness of MSME Business Processes - Chen Mei; Nina Anis; Nong Chai (Journal of Loomingulisus ja Innovatsioon, 2026)
Background of the Study Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving economic growth, particularly in emerging economies. However, MSMEs often face challenges related to limited resources, outdated business processes, and inefficient operational practices. The implementation of information technology (IT) has emerged as a potential solution to improve business processes, streamline operations, and enhance competitiveness. Despite the benefits, many MSMEs remain hesitant or lack the knowledge to effectively adopt IT solutions. Objective of the StudyThis study aims to examine the impact of information technology implementation on the efficiency and effectiveness of business processes in MSMEs. The research seeks to identify key factors that influence the adoption of IT, as well as assess how it contributes to improving operational efficiency, decision-making, and overall business performance in MSMEs. Research Method A mixed-methods approach was used, combining qualitative case studies with quantitative surveys. The study surveyed 100 MSMEs across various sectors, focusing on their adoption of IT tools for operations such as inventory management, financial tracking, and customer relationship management. In-depth interviews were conducted with business owners and managers to gain insights into their experiences with IT implementation. Research Results The findings revealed that MSMEs that integrated IT solutions experienced notable improvements in process efficiency, reduced operational costs, and enhanced decision-making. Over 70% of surveyed businesses reported better inventory management and faster response times to customer needs. Moreover, businesses leveraging IT tools showed a significant increase in productivity and profitability. Conclusion The implementation of information technology significantly enhances the efficiency and effectiveness of MSME business processes. The research suggests that MSMEs should prioritize IT adoption to stay competitive in a rapidly evolving business environment. Government support and capacity-building initiatives could further accelerate the digital transformation of MSMEs.